Efficacy and safety of oral mifepristone on preinduction cervical ripening at term pregnancy prospective randomized control study - N. , Sunanda; Gidaganti, Shilpa M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical ripening is important prerequisite for induction of labour, induction is indicated when it is advantageous to mother and fetus. Successful induction of labour decreases caesarean rate. Beyond term pregnancy there will be placental insufficiency, it leads to complications such as oligohydramnios thereby cord compression, birth asphyxia, increased incidence of operative delivery. Induction at term pregnancy has the potential to improve the neonatal outcomes. Aim was to study the efficacy and safety of oral mifepristone on cervical ripening prior to induction of labor at term pregnancy and to compare the feto maternal outcome with control group. Methods: Total 112 pregnant women at term pregnancy, where pregnancy can be continued for another 48 hours with bishop score 4 or less were selected. Sample was equally divided into study group (56 women) to receive 200mg mifepristone and control Group group (56 women) to receive placebo orally. Bishop score was assessed at 24hours and 48hours. In women who did not enter labor spontaneously other modes of induction was done. Results: There is significant improvement in bishop score at 24 hr and 48hr in study group p value 0.001, 80.35% women in study group and 50 % women in control group delivered vaginally. 33.9% women of study group and 10.7% women of control group delivered spontaneously. Requirement of PGE2 gel and oxytocin was significantly lesser in study group, there was no significant adverse effect seen on mother and newborn compared to control group. Conclusions: Cervical ripening with mifepristone prior to induction of labour at term improves bishop score and decreases rate of failed induction and cesarean section rate, with good neonatal outcome.